Primary Sphenoidal Sinus Lymphoma with Initial Presentation as Unilateral Abducens Nerve Palsy Symptom - Xijing Mao; Lifang Jin; Bochi Zhu; Honghua Cui; Min Yao; Gang Yao (Case Reports in Neurological Medicine)
A 48-year-old man presented with 3 days of mild horizontal diplopia in the left direction, followed by the onset of headache 17 days later. A physical examination revealed isolated left abducens nerve palsy. Head computed tomography (CT) and magnetic resonance imaging (MRI) scans revealed soft-tissue density neoplasms that occupied the sphenoidal sinus and further invaded to destroy the clivus. Immunohistochemical staining of neoplasms was performed from biopsies samples. The pathological diagnosis was extranodal natural killer (NK)/T-cell lymphoma (ENKL), nasal type, associated with Epstein-Barr virus (EBV). The patient subsequently exhibited secondary symptoms (fever, night sweats), enlarged lymph nodes, renal metastases, and hemophagocytic syndrome, with clinical diagnosis stage IV of ENKL. The patient has a poor prognosis. This report is unique in two aspects: the unilateral abducens nerve palsy as the initial and isolated symptom of ENKL, and the primary sphenoidal sinus ENKL.